Adolescents' dietary behaviour: The interplay between home and school food environments. (1st August 2022) - Ryan, D.; Holmes, M.; Ensaff, H.
Abstract: In the UK, school food standards have looked to improve the nutritional profile of school food provision and the choices made; however, adolescents' choices tend to bias towards micronutrient poor and energy dense options. This study aimed to explore how adolescents make their school food choices, along with how they engage with their environments whilst selecting food. Seven focus group interviews took place with adolescents (n = 28; 13–14 years) in a secondary school in Northern England. Discussions with participants were audio-recorded, transcribed verbatim and then analysed using an inductive thematic approach. Six themes emerged from the data: (1) parents' and adolescents' roles in the home food environment, (2) burgeoning food autonomy, (3) school food choice factors, (4) social aspects of school food, (5) home versus school, (6) food knowledge & beliefs. Adolescents identified two distinct environments during the focus group discussions: the home and school environments. Adolescents juxtaposed the two, in terms of food provision, food choices, rules and customs surrounding food choice. This juxtaposition emerged as an indirect but important influence on adolescents' school food choices. The school and home environments both (in)directly influence adolescents' school food choices, which involve an integration of multiple, often conflicting influences. Adolescents may adopt a number of unhelpful dietary rationalisations as they try to manage and reconcile these influences. Consultation, together with consideration of relevant food choice models, is required to identify opportunities to influence adolescents' food choices at school.